(untitled) (Educational Perspectives Magazine (REPED), 2022)
This Reflexive work takes the as a purpose to oriéntate the look of the education and of the teachers, on the Emotions inside and out of the classroom, not thinking that these are slightly related to the feelings but as a way of transformation in the living together, of the respect of other one since(as,like) legitimately other one(different). Inspired by the educations of the Doctor Humberto Maturana R. on the theory of the knowledge and the biological bases of the human understanding, it is focused on that the teachers and teachers have in all to the moment to plan the method of leaming, planning in consideration the emotions as foundation of to live and of to coexist human being. Take charge of the responsibility that is necessary to receive this child or girl who manages to edúcate to the college, to receive yours needs in the respect for yes same. To open the educational understanding of the social role that plays the emotions in this to flow emotionally inside and out of the classroom, to do happy and responsible children and not producís of a measurement of contents.